Research on dynamic modeling and electromagnetic force centering of piston/piston rod system for labyrinth piston compressor. (September 2016) - Cheng, Junming; Zeng, Xiangjun; Liu, Zhan; Yu, Xiaoling; Feng, Quanke
Inside labyrinth piston compressor, the piston/piston rod system is main moving part. They suffer from very large periodically varying loads caused by gas force and inertia force. This may result in the piston rod's bending and vibration. Therefore, the piston is always running eccentrically inside cylinder. It is difficult to calculate and predict the piston's eccentricity accurately by the traditional analytical method. However, an accurate radial clearance between the piston and the cylinder wall must be calculated in the early design of the labyrinth piston compressor. Thus, this article proposes a new numerical method of studying the piston's dynamic behavior, which is based on flexible body dynamics and finite element method. The method overall considers the piston rod's characteristics of bending and vibration, effect of the radial clearance between the piston rod and the guide bearing, as well as crosshead and slideway. Through the model, the piston's radial eccentric path can be better predicted. In addition, this article also introduces a new idea for realizing piston/piston rod system's centering and utilizing an electromagnetic guiding system instead of traditional mechanical structure. The new centering technology will simplify greatly the inner structure of the compressor by removing the guide bearing. We have designed theoretically the structure of an electromagnetic guiding system and built its control model. Simulation verifies the effectiveness of this method, and good control result is obtained.